Modulation of K+ translocation by AKT1 and AtHAK5 in Arabidopsis plants. (10th June 2019) - Nieves‐Cordones, Manuel; Lara, Alberto; Ródenas, Reyes; Amo, Jesús; Rivero, Rosa María; Martínez, Vicente; Rubio, Francisco
Abstract: Root cells take up K + from the soil solution, and a fraction of the absorbed K + is translocated to the shoot after being loaded into xylem vessels. K + uptake and translocation are spatially separated processes. K + uptake occurs in the cortex and epidermis whereas K + translocation starts at the stele. Both uptake and translocation processes are expected to be linked, but the connection between them is not well characterized. Here, we studied K + uptake and translocation using Rb + as a tracer in wild‐type Arabidopsis thaliana and in T‐DNA insertion mutants in the K + uptake or translocation systems. The relative amount of translocated Rb + to the shoot was positively correlated with net Rb + uptake rates, and the akt1 athak5 T‐DNA mutant plants were more efficient in their allocation of Rb + to shoots. Moreover, a mutation of SKOR and a reduced plant transpiration prevented the full upregulation of AtHAK5 gene expression and Rb + uptake in K + ‐starved plants. Lastly, Rb + was found to be retrieved from root xylem vessels, with AKT1 playing a significant role in K + ‐sufficient plants. Overall, our results suggest that K + uptake and translocation are tightly coordinated via signals that regulate the expression of K + transport systems. Abstract : AtHAK5 and AKT1 are expressed in root vascular tissues of K + ‐sufficient plants and contribute to Rb + (K + ) translocation in different ways: AtHAK5 promotes Rb + translocation whereas AKT1 has a negative role on this process by unloading Rb + from xylem sap.